ORGANIZATIONAL AND ECONOMIC ASPECTS OF IMPLEMENTING GENDER VERIFICATION METHODS IN HIGH-LEVEL SPORTS - Aleksandrovna Borodina, Mariya; Viktorovna Mashkova, Kseniya; Sergeevich Zenin, Sergey; Nikolaevich Suvorov, Georgiy (Gênero & Direito, 2020)
Organizational and economic aspects of implementing gender verification methods in high-level sports belong to controversial issues since they are concerned with the selection of methods for identifying the corresponding genetic characteristics of the human body. From the perspective of geneticists, endocrinologists and other medical workers, their implementation has long been criticized. To determine the prospects of using genetic achievements for gender verification in high-level sports, the authors of the article have considered the role of genetic information in the sports of the highest achievements and possible correction of borderline conditions; analyzed the methods used from the viewpoint of their reliability; assessed the costs of such genetic studies and examined their organization in the context of determining a competent subject and standardizing techniques and procedures. In contrast to the previous practice of gender verification, the current studies focus on changing testosterone levels and utilize different methods, some of which determine the level of total testosterone and the others define the level of free testosterone. Based on expert estimates, the authors have concluded that the method of tandem mass spectrometry is the most effective. Since the International Association of Athletics Federations allows the medical treatment of testosterone levels as a condition for admission to international competitions, the ongoing studies cannot be limited to identifying its quantitative indicators. An additional objective is to reveal the causes of hyperandrogenism, i.e. to expand the list of the methods used whose application should be unified with due regard to modern medical advances. From the economic viewpoint, measuring testosterone levels is not expensive but the costs will inevitably increase 10-15 times for identifying the causes of hormonal imbalances.